Kekuatan Perjanjian Internasional Terhadap Negara Yang Telah Meratifikasi: Analisis Kasus Sengketa Laut Cina Selatan - Muhammad Yogi Nofran; M. Azzah Rozanda; Firdhan Azhim Akbar (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study analyzes the binding force of international treaties on ratifying states, focusing on the People's Republic of China's (PRC) rejection of the 2016 Permanent Court of Arbitration (PCA) Award in the South China Sea dispute. Despite ratifying the United Nations Convention on the Law of the Sea (UNCLOS) 1982, China rejected the arbitral award won by the Philippines. This normative legal research employs statutory, case, and conceptual approaches with prescriptive-analytical analysis. The findings indicate that ratified international treaties possess binding force based on the principles of pacta sunt servanda and good faith as stipulated in the Vienna Convention 1969. China's rejection of the PCA award constitutes a violation of Article 296 UNCLOS, which mandates compliance with dispute settlement decisions. Legal implications of this rejection include breach of international obligations, undermining the credibility of the international legal system, and setting negative precedents for other states. However, limitations in international law enforcement mechanisms remain a primary challenge in ensuring state compliance with treaty obligations.